History of public libraries for children (to 1914) - Walczak-Niewiadomska, Agata (Interdyscyplinarium nauk o mediach i kulturze, 2020)
For many years, librarianship and children’s librarians have been treated by historians and researchers as an area that does not require attention. They have been even ignored in the vast compendiums about public librarianship. Polish studies presenting beginnings of children’s librarianship in the world, have been published after the Second World War, but most often as short contributions. Meanwhile, the directions of developing services for this group of readers constitute an interesting example of implementing this idea in the other countries. The aim of the article is to supplement the state of knowledge in the Polish literature about the beginning of library services for children and further development of this branch of public librarianship. Pioneer countries (United States and Great Britain) will be taken into account, as well as other countries, which until 1914 have taken over the ideas (e.g. Belgium and Scandinavian countries). The issues presented in the article were developed using the method of critical analysis of the subject, based on materials published mainly abroad. Both the progressive improvement of living conditions of the middle class and the activities of feminist organizations were important for the development of children’s librarianship in the United States and the European countries. Historical sources repeatedly point out a repetitive pattern showing the transfer of ideas taken from United States to other countries by individual educators. This way, the concept of children’s librarianship developed in most European countries at the turn of the 19th and 20th centuries, as well as in other parts of the world in later years.